ANALYSIS OF THE INTEGRATION OF ISLAMIC EDUCATION IN MABNA AR RAZI: PERSPECTIVE OF SEYYED HOSSEIN NASR - Al Farabi, Moh Rifqi Falah; Muhammad, Nawawi Aulia; Fauzi, Ahmad; Syaifuddin, Helmi (HUNAFA Jurnal Studia Islamika, 2024)
This research describes the analysis of the integration of Islamic education at Mabna Ar Razi: Seyyed Hossein Nasr's perspective, how education is implemented at Mabna Ar-Razi, and what the mahasantri's perspective is regarding education implemented at Mabna Ar-Razi. This type of research is descriptive qualitative research, a case study type. The subject of this research is mahasantri mabna Ar-Razi. Data collection techniques used educational observations at Mabna Ar-Razi, and interviews with Mahasantri and Musyrif Mabna. Apart from that, it also documents the schedule of activities at Mabna Ar-Razi. Data analysis uses the Miles, Huberman, and Saldana model. The results of this research are (1) the implementation of education at Mabna Ar-Razi combines intellectual and religious intelligence and character education. (2) Students' perspectives on education at Mabna Ar-Razi show a positive response, where they feel that education at Mabna provides a deep understanding of Islamic values ​​and helps them apply these teachings in their daily lives.